EFFECTS OF THE HEAVY METAL, ZINC, ON THE FRESHWATER FISH TILAPIA NILOTICA L. - VIRGINIA S. CARING (Biotropia: The Southeast Asian Journal of Tropical Biology, 2011)
Gills, gonads, and blood of Tilapia nilotica exposed to different concentrations of zinc sulfate (ZnSO4. 7H2O) exhibited histological effects. Gills of posthatch larvae exposed chronically  for 21 days  to 2 ppm zinc sulfate and fingerlings to 10 ppm sublethal zinc concentrations exhibited hyperplasia that resulted in fusion of adjacent secondary gill lamellae. The same effects were observed  in 4-hour short-term exposure  to 30 ppm lethal dose. Posthatch  larvae  subjected  to  2  and  5  ppm  sublethal  levels  of  zinc  for  30  days  retained undifferentiated  gonads  with  differentiation  with  oogonial  proliferation.  Ovaries  of  control  fish demonstrated healthy oocyte growth and other normal histological features after 57 days. In contrast, ovaries in treated groups exhibited excessive amounts of connective tissue, hyperemia and markedly reduced oocyte number. Oocytes had wavy irregular surface outlines. Deviation from normal was observed to be dose dependent. In juvenile tilapia, spermatogenesis was observed in control testes. Testes of zinc-exposed fish, on the other hand, remained immature. Hyperemia was markedly pronounced in both testes and ovary after 90 days exposure to zinc. Blood of Tilapia nilotica fingerlings exposed to sublethal concentrations of 2, 5, and 10 ppm zinc for 30, 60,  and  90  days  exhibited  anisocytosis  and  poikilocytosis. There was  an  increase  in  hematocrit  values  in zinc-reared  fish which, however,  reverted  to  control/near  control  levels at day 90. Hemoglobin  values were inversely proportional to the level of zinc in the rearing water. The marked reduction in hemoglobin values in fish reared at the higher zinc concentrations of 5 and 10 ppm suggests the development of some degree of anemia which is also supported by the observations of anisocytosis and poikilocytosis.